THE MAIN THEORETICAL FEATURES OF SPEECH COMMUNICATION IN TEACHING - Anarkulova Guzal Abdurashid Qizi (Western European Studies, 2024)
This article is intended to give basic information on the fundamentals of speech communication to students who have little or no background in communication theory. It is essential and much more useful to help the students understand the pervasiveness of communication in their lives, to demystify the theoretical process, and to help students become more systematic and critical in their thinking about theory. Also there are given main features of communication and its various aspects in speech communication. Much attention has been paid to the analysis of communication component, forms and types as well as the models of communication
Keywords: The academic study of communication; communication theory; communicology